The development of students’ adversity quotient through online learning models: A case study of an Islamic education course - Dina Mardiana; Tobroni Tobroni; Triyo Supriyatno (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2021)
Students’ Adversity Quotient is one of the most significant elements in online education. This research focused on analyzing how the design of learning of an online Islamic education course called Pendidikan Agama Islam (PAI) prepared the development of students’ adversity quotient. This research was located at a university in Malang, Indonesia and its methodology used qualitative case study. Based on Stoltz's Adversity Quotient theory (Stoltz, 1997), data collection for this study was carried out through online-based interviews, participant observation, and documentation. However, interactive model of Miles, Huberman, and Saldana (Miles, et al., 2014) was used as data analysis. The research found that the PAI course at a university in Malang had a theoretical learning model, which could develop students’ adversity quotient. The theoretical learning model of PAI requires an ability to adapt cognitive structures through the stages of assimilation, accommodation, and equilibration of new knowledge, as well as psychic readiness to face challenges providing the development of students' adversity quotient. This theoretical learning model facilitated the development of students’ adversity quotient, as emerged through four indicators: resilient, persistent, sincere, and self-gratefulness. The contribution of this research is crucial to the implementation of online Islamic education learning through a theoretical learning model that will lead to benefits in achieving educational targets more effectively.